2005
DOI: 10.1007/s00531-005-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

The Mesozoic–Cenozoic structural framework of the Bay of Kiel area, western Baltic Sea

Abstract: A dense grid of multichannel high-resolution seismic sections from the Bay of Kiel in the western Baltic Sea has been interpreted in order to reveal the Mesozoic and Cenozoic geological evolution of the northern part of the North German Basin. The overall geological evolution of the study area can be separated into four distinct periods. During the Triassic and the Early Jurassic, E-W extension and the deposition of clastic sediments initiated the movement of the underlying Zechstein evaporites. The deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 18 publications
7
51
0
Order By: Relevance
“…We assume that this fault reaches the seafloor. Bak-Hansen et al (2005) observed such faults in this region affecting the seafloor using higher frequency seismic data and smaller shot-receiver separations. In general, the study area lies between the Glückstadt Graben and the Vorpommern Fault system and is relatively unaffected by brittle faulting.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We assume that this fault reaches the seafloor. Bak-Hansen et al (2005) observed such faults in this region affecting the seafloor using higher frequency seismic data and smaller shot-receiver separations. In general, the study area lies between the Glückstadt Graben and the Vorpommern Fault system and is relatively unaffected by brittle faulting.…”
Section: Discussionmentioning
confidence: 93%
“…The distribution of the Cenozoic sediments shows an overall thickening trend towards the center of the basin in the south to southwest (Bak-Hansen et al 2005). On top of the Fehmarn Pillow, the Cenozoic succession is actually absent, pointing to reactivated vertical salt movement observed towards the end of the Late Cretaceous that must have continued throughout the Cenozoic.…”
Section: Geological and Structural Settingmentioning
confidence: 95%
See 2 more Smart Citations
“…During these research cruises, a dense grid of high-resolution multichannel seismic data was acquired. The first outcome of this effort was the description of the post-Permian evolution of the Bay of Kiel (Hansen et al, 2005). Seismic interpretation allowed the reconstruction of the impact of the main tectonic phases, i.e.…”
Section: Introductionmentioning
confidence: 99%